[Kościół św. Jana w Gdańsku] [aut. odb. Karol Nowaliński]. - Nowaliński, Karol (1935- ). (Karol Nowaliński, 1986)
Przedstawia fragment kościóła Św. Jana od poł. wschodu, na pierwszym planie fragment ul. Świętojańskiej (Johannisgasse), ok. 1900 r.